Emerging therapy in light-chain and acquired transthyretin-related amyloidosis: an Italian single-centre experience in heart transplantation. Issue 4 (27th April 2021) - Di Nora, Concetta; Sponga, Sandro; Ferrara, Veronica; Patriarca, Francesca; Fanin, Renato; Nalli, Chiara; Lechiancole, Andrea; Vendramin, Igor; Livi, Ugolino
Abstract : Aims: The prognosis for patients affected by light-chain cardiac amyloidosis and acquired transthyretin-related (TTR) amyloidosis is poor. Heart transplantation (HTx) could improve prognosis also enabling autologous stem cell transplantation (ASCT) in the first group. Methods and results: A total of 36 patients affected by systemic amyloidosis have been referred to our centre from 2009 to 2019. Of these, nine had cardiac involvement: seven by light-chain amyloidosis and two by acquired TTR amyloidosis. None died while waiting for HTx. A specific internal protocol useful to select candidates and to monitor the organ involvement after HTx was developed. Median age at diagnosis was 54 years and 66% were male. The most common short-term complication after HTx was renal failure (44%), followed by acute cardiac rejection more than 2R (22%). ASCT was performed in six out of seven light-chain cardiac amyloidosis patients, with a median time of 6 months after HTx. Two patients affected by light-chain cardiac amyloidosis died due to amyloidosis relapse: one before undergoing ASCT. After a median follow-up of 31 (7–124) months, 1- and 5-year survival was 88 and 66% in the cardiac light-chain amyloidosis group. Conversely, 1- and 5-year survival was 100% in the acquired TTR amyloidosis group. Conclusion: HTx may represent a valuable option in carefully selected patients. ASCT after HTx is an effective treatment that could decrease amyloidosis relapse in light-chain cardiac amyloidosis patients. A multidisciplinary approach is mandatory to select the best candidates and to obtain the most effective results with a specific surveillance follow-up protocol.